Funny weather : art in an emergency - Laing, Olivia (W.W. Norton & Company, 2020)
"One of the finest writers of the new non-fiction" (Harper's Bazaar) explores the role of art in the tumultuous twenty-first century. In the age of Trump and Brexit, every crisis is instantly overridden by the next. The turbulent political weather of the twenty- first century generates anxiety and makes it difficult to know how to react. Olivia Laing makes a brilliant, inspiring case for why art matters more than ever, as a force of both resistance and repair. Art, she argues, changes how we see the world. It gives us X-ray vision. It reveals inequalities and offers fertile new ways of living. Funny Weather brings together a career's worth of Laing's writing about art and culture, and their role in our political and emotional lives. She profiles Jean-Michel Basquiat and Georgia O'Keeffe, interviews Hilary Mantel and Ali Smith, writes love letters to David Bowie and Wolfgang Tillmans, and explores loneliness and technology, women and alcohol, sex and the body. With characteristic originality and compassion, Funny Weather celebrates art as an antidote to a terrifying political moment"--